Pengaruh Bermain Konstruksi Terhadap Tingkat Kecemasan Anak Usia Sekolah Yang Menjalani Hospitalisasi Di Ruang C6 RSUD Cibabat Cimahi - Andri Nurmansyah; Fifi Siti Fauziah Yani; Roganda Situmorang (MOLUCCAS HEALTH JOURNAL, 2022)
The world of children is a world of play. The purpose of playing in a hospital is in principle to be able to continue the optimal growth and development phase, develop children's creativity, and children can adapt more effectively to stress. One of the types of games for children is playing construction. Playing construction is aimed at compiling a game object so that it becomes a correct construction like a game of assembling blocks. Treatment of children in hospitals forces children to be separated from the environment they love, namely family. The impact of separation from the family, children experience psychological disorders such as anxiety, fear, lack of love, these disorders can hinder the child's healing process and interfere with the child's growth and development. This study aims to determine the effect of construction play on the anxiety level of school-age children who are undergoing hospitalization. This study uses a type of pre-experimental research, which is a part of experimental research conducted without a control variable. The design used in this study was a pre test - post test one group design. The effect of construction play on the anxiety of school-age children undergoing hospitalization can be measured using the McMurtry Faces Anxiety Scale For Children which was tested before and after giving construction play. In accordance with the results of the Wilcoxon test with a 95% confidence level (α = 0.05) the p value is 0.0001, thus the p value <α (0.0001 <0.05), then Ho is rejected Ha is accepted. There is an effect of giving construction play on the anxiety of school-age children undergoing hospitalization in Room C6 of Cibabat Hospital, Cimahi